Prospek Hukum Islam dalam Sistem Hukum Indonesia - Saifuddin, Saifuddin (al-'adalah, 2017)
Although the majority of Indonesian citizens are Muslims, Islamic law cannot automatically apply in this country. This is because Indonesia is not a religious state and does not make religion as the state's ideology. This article analyzes the prospects of tranformation of Islamic law into the national legal system. The aim is to find a format that is in accordance with the character of the Indonesian state and does not deviate from state idiology of Pancasila . This study concludes that there are only a few ways to enforce Islamic law in Indonesia without changing the existing state order. First: through a constitution amendment. Islamic law can be transformed into positive law insofar as it is accepted by the legislative body through democratic ways. Second: through the transformation of legal material. This method is carried out by changing the material law based on secular values into a legal product based on Islamic values. Third: through regional autonomy. such as in Aceh, Banten, Madura, and Gorontalo.